The lifetime of interlayer breathing modes of few-layer 2H-MoSe2 membranes - Soubelet, Pedro Ignacio (2019)
A time-resolved observation of coherent interlayer longitudinal acoustic phonons in thin layers of 2H-MoSe2 is reported. A femtosecond pump-probe technique is used to investigate the evolution of the energy loss of these vibrational modes in a wide selection of MoSe2 flakes with different thicknesses ranging from bilayer up to the bulk limit. By directly analysing the temporal decay of the modes, we can clearly distinguish an abrupt crossover related to the acoustic mean free path of the phonons in a layered system, and the constraints imposed on the acoustic decay channels when reducing the dimensionality. For thicker samples, the main acoustic attenuation mechanism is attributed to the scattering of the acoustic modes with thermal phonons. For samples thinner than ∼20 molecular layers, the predominant damping mechanism is ascribed to the effects of surface asperity. Losses intrinsic to the low dimensionality of single or few layer materials impose critical limitations for their use in optomechanical and optoelectronic devices.